Determining motivators and hygiene factors among excellent teachers in Malaysia: An experience of confirmatory factor analysis. Issue 2 (13th March 2017) - Amzat, Ismail Hussein; Don, Yahya; Fauzee, Sofian Omar; Hussin, Fauzi; Raman, Arumugam
Abstract : Purpose: In a world in which successful learning is believed to rest on the methods of teaching and the performance of students is determined by teacher quality, it is clear that teachers are the backbone of student learning attainments. In such a scenario, teacher development, welfare, motivation, and satisfaction are crucial for better teaching performance. Therefore, the purpose of this paper is to determine the motivator and hygiene factors among excellent teachers in Malaysia and to explore factors that lead to satisfaction and cause dissatisfaction among excellent teachers in Malaysia. Design/methodology/approach: This study uses quantitative design to determine the motivator and hygiene factors among excellent teachers. For the sample size, 306 excellent teachers participated in this study and data were analysed using principle component analysis and confirmatory factor analysis to determine the dominant factor among Herzberg's motivator and hygiene factors. Findings: From the findings, the results showed that the satisfaction of excellent teachers was low in terms of "personal growth" (motivator) and "supervision" (hygiene). The paper concludes by calling upon the Malaysian Ministry of Education (MoE) to consider both motivator and hygiene factors, and what causes satisfaction and dissatisfaction among excellent teachers. Research limitations/implications: This study has some limitations to be considered, especially in terms of sample size. The low number of excellent teachers participating in this study is due to the scarcity of face-to-face data collection, in that an online survey was deemed to be the only means to reach the excellent teachers. This is due to the lack of a list of excellent teachers in some state districts, making it difficult to determine those schools which have excellent teachers. In addition, it is also due to logistical and geographical difficulties in reaching certain schools and meeting the excellent teachers. In recognition of such difficulties in undertaking research on excellent teachers in Malaysia, the researchers in this study urge the Malaysian MoE, as well as state districts and regional offices, to update the profile of excellent teachers by creating records and a list of all excellent teachers in Malaysia to facilitate future research. In this scenario, the findings of this study should be used with caution and not be generalized to other contexts, schools, regions, or states. Practical implications: To be fully cognizant about the excellent teachers' scheme was introduced to uplift the standard of teaching in Malaysia, and the recipients of this scheme or status (excellent) are considered to be the "cream of the crop" in the teaching profession in Malaysia and for non-excellent teachers to emulate, it is vital to look into their well-being as well as their growth. With the results of this study, the authors can say that the implications for practice touch many aspects of the professional and personal development of Malaysian excellent teachers. Specifically, it is imperative that the factors that intrinsically and extrinsically motivate excellent teachers in Malaysia and the causes of dissatisfaction are identified. In addition, the implications also place emphasis on paving ways for the personal growth of excellent teachers and to provide leeway for them to pursue their own personal happiness. Furthermore, the implications of the lack of proper supervision of school principals on excellent teachers should be avoided, and, in general, hygiene factors could be used as positive implications to improve excellent teachers' teaching practices and performance. Originality/value: This research is original as it calls MoE attention to the well-being of excellent teachers in Malaysia. As excellent teachers in Malaysia are selected and promoted among teachers in Malaysia in order to improve teaching and learning in Malaysia. They are appointed to be a role model for other teachers to emulate. With this position, excellent teachers are expected to contribute to the development of their schools and others and they can be posted anywhere as well as called at any time for help. Therefore, it is worthy to know how satisfied those excellent teachers are regarding government policy. Hence, it is important to know what motivates and satisfies them.